An Investigation On The Relationship Between Writer's Block and Writing Apprehension Among ELT Undergraduates In UNIMAS - Caroline, Lee Ai Nguk (Universiti Malaysia Sarawak (UNIMAS), 2007)
There are times when undergraduates can only write very little or none at all despite their effort, their basic writing skills and linguistic competence. When this happens, the undergraduates are actually experiencing a writing dysfunction termed Writer's Block. This study seeks to investigate the relationship between Writer's Block and Writing Apprehension among ELT undergraduates. Specifically, it seeks to investigate the cognitive factors related to the writing dysfunction when they write assignments in English. Adapted versions of the Writer's Block Questionnaire developed by Rose (1984) and the Writing Attitude Test developed by Daly-Miller (1975a) were incorporated into one and administered to I I I ELT undergraduates in UNIMAS. The results were analysed. Respondents who have high and low levels of Writer's Block and Writing Apprehension were selected for the semi-structured interview. Their responses were transcribed and analyzed. The results suggested that the main causes of the Writer's Block among the ELT undergraduates were their attitude towards writing, the complexity of the task and the lack of academic writing strategies. The problem was also found to be closely related to the undergraduates' language competency and their environment.